Application of the Waterfall Method in Creating Payroll Applications Based on Java Netbeans - Pratama, Muhamad Bayu Aditya; Hilabi, Shofa Shofia; Ihsan, Mohammad Maftuh; Ferdiansyah, Indra; Nizar, Hafiz Saefun (Cattleya Darmaya Fortuna, 2024)
This study explores the application of the Waterfall methodology in developing a payroll application based on Java Netbeans. The Waterfall methodology, known for its sequential and linear approach to software development, is implemented to guide the development process of the payroll application. Java Netbeans serves as the development environment for building the application, leveraging its comprehensive features and compatibility with the Java programming language. The study aims to analyze the effectiveness and challenges encountered in employing the Waterfall methodology specifically in the context of developing a payroll application. Through a systematic examination of the development process, this research provides insights into how the Waterfall methodology can be adapted and utilized effectively in the creation of software applications, particularly in the realm of payroll management. The use of Java Netbeans as the development environment provided advantages in using its extensive features and good compatibility with the Java programming language. The findings also highlighted some of the challenges encountered, including possible difficulties in adjusting to changes in application needs or requirements during the linear development process. Overall, however, the application of the Waterfall method in the creation of the Netbeans Java-based payroll application provided a solid foundation for effectively managing the project and producing an application that met user needs.